Case in Batam City: The Crime of Electronic Gaming in The Industrial Revolution 4.0 Era - Manurung, Kristie Sugama; Amboro, F. Yudhi Priyo; Hutauruk, Rufinus H. (Widya Yuridika, 2023)
Gambling presents several problems, including the possibility that some people will develop an addiction, an inability to stop gambling, and significant financial loss. Therefore, it is evident that gambling is detrimental to individuals and can harm society as a whole. It will also have the potential to reduce the community's economy. In the city of Batam, online gambling is commonplace and familiar. Online gambling has penetrated society from the upper classes to the lower classes. Several factors cause gambling, which is closely related to the factors that cause crime. The two main types of factors that can lead to criminal behaviour are those that come from outside the individual (external) and those that come from within the individual (internal), such as psychological, educational, and religious factors. Association and family environment. This type of research is Normative Juridical Research with a statute approach. Normative legal analysis is also known by another term, namely doctrinal legal research. This research shows that Indonesia's Law on Information and Electronic Transactions has not been fully effective. This is in line with the theory of Legal Effectiveness put forward by Soerjono Soekanto. Judging from the legal factors themselves, which are only limited by law, the government must pay more attention to aspects of legal certainty regarding gambling regulations so that they are by social values that view all forms of gambling as dangerous.